Testing of insulated sandwich panels with GFRP shear connectors. (15th April 2020) - Hou, Hetao; Wang, Wenhao; Qu, Bing; Dai, Chunxue
Highlights: The GFRP shear connectors with solid and non-solid webs can be both used. An analysis model to capture the cracking behavior of the panel was established. An analysis model to calculate the ultimate resistance of the panel was established. Abstract: This paper focused on the panel which sandwiches an Expanded Polystyrene (EPS) layer between two Steel Reinforced Concrete Layers (SRCLs). The EPS layer provides thermal insulation in the panel while the two exterior SRCLs are connected by Glass Fiber Reinforced Plastic (GFRP) shear connectors to form the composite action and hence achieve a higher flexural resistance in the panel. Four types GFRP shear connectors which consist of diagonal web members, webs with circular perforations, webs with slotted perforations and solid webs, respectively, were considered in this research. To experimentally address the flexural responses of the panels with the four types of GFRP shear connectors, four full-scale experimental specimens were constructed and tested. The test results show that generally any of the four GFRP shear connectors can enable the panel to exhibit satisfactory flexural performance although the GFRP shear connectors with the solid webs tend to increase the ultimate flexural resistance of the panel. Beyond the experimental work, an analysis model based on the transformed cross-section approach and elastic beam theory was developed for capturing the flexural response of the panel up to the cracking limit state. Moreover, an analysis model based on the assumed strain and stress diagrams was established to compute the ultimate flexural resistance of the panel.